Fish species richness and habitat quality mapping with GIS across Cauvery River in Tamil Nadu, India - Arunkumar, Anbu Aravazhi; Manimekalan, Arunachalam; Manikandan, Velu; Velmurugan, Palanivel (Journal of Aridland Agriculture, 2016)
Geographical Information System (GIS) is associated as an essential tool and as a part of natural resource management activities worldwide. Though, GIS is receiving special attention in the field of hydrology and the aquaculture management, their deployment for spatial decision support in this domain continues to be very slow. This situation is owing to a variety of constraints together with an absence of appreciation of the technology, restricted understanding of GIS principles and associated methodology, and inadequate structure commitment to confirm continuity of these spatial decision support tools. This paper addresses these constraints and includes the use of basic GIS techniques. Fish and water samples were collected and analyzed from seven sites along the Cauvery river basin, Tamilnadu, India and the results were incorporated into GIS platform. The section on GIS terminology addresses the two fundamental types of GIS (Mapping and Interpretative analysis), and discusses the aspects related to the visualization of outcomes. Spatial distribution maps were prepared for the above analyzed parameters. Inverse Distance Weighting (IDW) tool have been applied to express the results obtained from the study area.